2022
DOI: 10.1108/pr-01-2021-0032
|View full text |Cite
|
Sign up to set email alerts
|

Insider perspectives on director remuneration governance deliberations

Abstract: PurposeCompanies around the globe increasingly receive immense shareholder scrutiny due to perceivably excessive executive director remuneration. The debate in South Africa intensifies due to severe pay inequality. The authors thus accounted for the perspectives of asset managers and listed financial services companies in South Africa pertaining to the impact of voting and engagement on director pay policies and practices.Design/methodology/approachSemi-structured interviews were conducted with selected asset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(150 reference statements)
0
0
0
Order By: Relevance
“…There are several studies on the independence of nomination and remuneration committees, such as Van Zyl and Mans-Kemp (2023) who found that independent remuneration committees have an important role in facilitating relationships with investors to ensure fair remuneration. Ruigrok et al .…”
Section: Dimensions Of the Nomination And Remuneration Committeementioning
confidence: 99%
“…There are several studies on the independence of nomination and remuneration committees, such as Van Zyl and Mans-Kemp (2023) who found that independent remuneration committees have an important role in facilitating relationships with investors to ensure fair remuneration. Ruigrok et al .…”
Section: Dimensions Of the Nomination And Remuneration Committeementioning
confidence: 99%